Synthesis and characterization of La-doped and La-I co-doped TiO2 photocatalysts for photocatalytic degradation of Methylene Blue Dye from its aqueous solution - Verma, Veeresh (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Chemical Engineering and Technology